Experience from therapeutic drug monitoring and gender aspects of gabapentin and pregabalin in clinical practice. (May 2015) - Johannessen Landmark, Cecilie; Beiske, Georg; Baftiu, Arton; Burns, Margrete L.; Johannessen, Svein I.
Highlights: Gabapentin and pregabalin are more used in women than in men. Routine use of TDM is most common in patients with epilepsy; not other indications. Pharmacokinetic variability ( C / D -ratio) was >100-fold for both drugs. There is a need for reevaluation of the reference range of gabapentin. Individualisation of therapy with TDM is important regardless of indication. Abstract: Purpose: Gabapentin and pregabalin are antiepileptic drugs (AEDs) with epilepsy and neuropathic pain indications. The purpose of this study was to investigate pharmacokinetic variability of gabapentin and pregabalin and indications for therapeutic drug monitoring (TDM) in clinical practice with focus on gender aspects. Method: Anonymous data from routine TDM-service at the National Center for Epilepsy regarding serum concentration measurements of gabapentin and pregabalin, 2009–2013, were utilised. All included samples were drug-fasting in the morning at steady-state. Results: In total, 356 patients were included; gabapentin 189 (66% women), average age 53 years and pregabalin 167 (56% women), average age 50 years. For gabapentin, mean serum concentration/dose( C / D )-ratio was similar across genders. Only 13% of the patients had concentrations above the lower limit of the reference range (70–120 μmol/L), which indicates a need for reevaluation of the reference range. For pregabalin, the C / D -ratio in women (0.08 ± 0.06) was 42% higher than in men (0.056 ± 0.05; p  < 0.05). The pharmacokinetic variability ( C / D -ratio) was >100-fold for both gabapentin and pregabalin. An indication of use (epilepsy/pain/other) was stated in only 26% of the cases ( n  = 94). Epilepsy was assumed as indication when other AEDs were also measured (50% of patients). This was similar for both genders and for both AEDs. Indications for TDM were stated in 155 cases (44%) and were similar for gabapentin and pregabalin. Conclusion: Gabapentin and pregabalin are more used in women than in men, and routine use of TDM is most common in patients with epilepsy. Pharmacokinetic variability is extensive, highlighting a need for individualisation of therapy regardless of indication.